THE INDONESIAN MEDICAL DISCIPLINE HONOUR COUNCIL (MKDKI) AS THE DEVELOPMENT OF A MEDICAL DISPUTE RESOLUTION MODEL IN THE PERSPECTIVE OF DEMOCRATIC LAW - Nur Husein Amrah; Hotma P. Sibuea; Ika Dewi Sartika Saimima (Bhayangkara Law Review, 2024)
Law Number 17 of 2023 concerning health has regulated the position of MKDKI in resolving medical disputes. The MKDKI's authority in the Health Law has been expanded to relate to violations of doctor's discipline, enforcing decisions regarding unlawful acts that can be subject to criminal sanctions, and enforcing accountability for actions/deeds that cause civil harm to patients. Based on this authority, MKDKI is similar to an institution that acts on the principles of fast, simple and low-cost justice. To study the MKDKI model, normative juridical research or doctrinal research is used. The study that will be discussed concerns the interpretation of the legal principles of law enforcement regarding alleged medical malpractice which contains violations of criminal law. The results of the research state that the MKDKI's authority, which is based on the process of resolving medical disputes using the principles of fast, simple and low cost, is less effective. Supreme Court Decision Number: 890K/Pid.Sus/2017 is an example of a legal solution that actually harms doctors. It is necessary to transform MKDKI into a strong institution, with a pattern of resolving medical disputes using fast, simple and low-cost principles. A medical dispute resolution model based on the principles of fast, simple and low cost will only emerge if a Medical Court is established. MKDKI as Medical Justice aims at enforcing acts that violate criminal law and enforcing responsibility for actions/deeds that cause civil harm. The MKDKI's independence, such as independent judicial power, to the MKDKI's objection filing system which adopts an appeals filing system within the judiciary, further emphasizes the need to transform the MKDKI as a judicial institution.